Approaches to assessing and minimizing blood wastage in the hospital and blood supply chain - Yates, Nicola; Wilding, Richard D. (Wiley, 2017)
Despite the scale of blood usage worldwide, blood remains a scarce and precious resource. As with any perishable product, careful management of inventories to minimize wastage is crucial. However, due to the nature of the supply of blood, wastage is not only an economic issue as every unit wasted, squanders the time and effort of the human donor. Blood inventory management is therefore a trade-off, ensuring 100% availability of all blood products at all times whilst minimizing wastage. Hospitals are at the front line of blood use and are the location where much blood is wasted. Inventory management practices in hospital transfusion laboratories are critical. Much of the extant literature in this area posits that good management of hospital blood inventories is due to sophisticated inventory models and algorithms. However, recent research has found that good management practices are much more important. The drivers for low wastage and good inventory management practice can be described using six key themes. Blood supply chain management is much more than managing wastage in hospitals. Proper management of the supply chain as a whole can lead to significant reductions in blood wastage. Recent research has found that methods commonly used in commercial supply chain management can lead to efficiencies in the blood supply chain context. An example of this is stock sharing or lateral transhipment of blood units close to expiry between hospitals, reducing wastage across the supply chain.
Keywords: Blood processing; Red cells; Transfusion medicine